2018
DOI: 10.1016/j.redox.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

A single cysteine post-translational oxidation suffices to compromise globular proteins kinetic stability and promote amyloid formation

Abstract: Oxidatively modified forms of proteins accumulate during aging. Oxidized protein conformers might act as intermediates in the formation of amyloids in age-related disorders. However, it is not known whether this amyloidogenic conversion requires an extensive protein oxidative damage or it can be promoted just by a discrete, localized post-translational modification of certain residues. Here, we demonstrate that the irreversible oxidation of a single free Cys suffices to severely perturb the folding energy land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…15a ). 41 , 42 In vitro binding assays showed that similar levels of SMYD2 WT and C13D were bound to Hsp90 and N2A (Supplementary Fig. 15c–d ).…”
Section: Resultsmentioning
confidence: 94%
“…15a ). 41 , 42 In vitro binding assays showed that similar levels of SMYD2 WT and C13D were bound to Hsp90 and N2A (Supplementary Fig. 15c–d ).…”
Section: Resultsmentioning
confidence: 94%
“…The benzothiazole dye ThT, which displays enhanced fluorescence when it binds to beta sheet-rich structures in amyloids, is widely used as a probe for protein unfolding and aggregation [ [46] , [47] , [48] ]. Native AN showed a high fluorescence emission intensity at 495 nm consistent with ThT binding, and the presence of hydrophobic patches and a beta-sheet structure on the protein surface ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the decrease of GSH level has been shown to induce cognitive decline and neuronal death during aging and neurodegenerative diseases [53,54]. Interestingly, P2X7R is a therapeutic target in the treatment of epilepsy [12][13][14]55].…”
Section: Discussionmentioning
confidence: 99%